MECHANISMS FOR DEVELOPING INFORMATION COMPETENCE OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the pedagogical significance of using information and communication technologies and digital learning tools in developing the creative activity of students and future teachers in higher education institutions. The study analyzes the content of information competence, including its connection with searching, selecting, analyzing, processing, storing, transmitting, and adapting information to educational processes. The article also reveals the interrelation between information culture and information competence, their role in teachers’ professional competence, and the necessity for educators to use digital technologies effectively in the modern information society. Particular attention is paid to the possibilities of computer technologies, mobile devices, interactive tools, web services, and digital educational environments in organizing teachers’ innovative professional activity. The findings indicate that the formation of information competence is an essential condition for increasing the creative potential of future teachers, preparing them for independent learning, and ensuring the effectiveness of professional pedagogical activity.